AKUMULASI KASUS PELANGGARAN HAM BERAT DI PAPUA PADA MASA KEPEMIMPINAN PRESIDEN B.J. HABIBIE S.D. SUSILO BAMBANG YUDHOYONO DALAM PERSPEKTIF HUKUM INTERNASIONAL - Standy Wico; Dylan Aldianza Ramadhan; Anastasia Anastasia; Vindy Kusuma; Vivia Chandra; Vera W. S. Soemarwi (Jurnal Hukum Adigama, 2021)
The government must respect the human rights of every person in Indonesia. From many islands in Indonesia, there are several areas that are given special status, one of which is Papua. The government gives privileges because Papua is an area that is located at the very end of Indonesia and is vulnerable to provocations from outsiders. Of all the presidents who have served in Indonesia, they are very focused on addressing this issue. All efforts have been made and not infrequently these efforts are contrary to the law. The forms of legal violations that occur are dominated by violations of Human Rights (HAM). Talking about human rights violations, this cannot be separated from the view of international law. The international party is a very influential party in efforts to eliminate every act of crime against humanity. The issues that will be discussed regarding the gross human rights violations that occurred in Papua during the leadership of President B.J. Habibie to President Susilo Bambang Yudhoyono and the perspective of international law in cases of gross human rights violations in Papua during the leadership of President B. J. Habibie to Susilo Bambang Yudhoyono. The research method used is normative research. The gross human rights violations that occurred in Papua have met the elements of international crimes. Based on the perspective of international law, the Indonesian government is considered to be responsible for the gross human rights violations that occurred in Papua.